Influence of earthquake angle on seismic performance of concrete highway bridges - Ahmet Can Altunışık; Ebru Kalkan Okur (Građevinar)
This study aims to evaluate the effect of earthquake angle on the seismic performance of a concrete highway bridge. As a numerical example, a twin prestressed concrete box-girder highway bridge was analysed using finite element methods. The bridge was subjected to the 1992 Erzincan earthquake ground accelerations in 19 directions with values ranging from 0° to 90° in 5-degree increments. To evaluate the effects of different earthquake angles on seismic performance, variations in the maximum displacements, internal forces and principal stresses on the bridge deck, columns, isolator and foundation were studied . The results changed considerably for different earthquake angles. Variations in the displacement, internal forces and principal stresses occurred at different incidence angles. In other words, there is no unique angle of incidence for each structure.